The Concept of Syntactic Dependencies and Its Impact on Understanding the Meanings of the Holy Quran in Ibn Ashur's "Tahrir wa Tanwir" Commentary - Hussein Zaatout; Abdel Salam (Rechtsnormen: Journal of Law, 2024)
Background. Quranic exegetes have endeavored to find appropriate mechanisms that can help unravel the mysteries of Allah's book and interpret Quranic verses correctly. Method. Rarely do we find a scholar who has a unique approach that provides unprecedented creativity in their interpretations. One of these exceptional scholars is Imam Muhammad Al-Tahir bin Ashur, the author of the tafsir "Tahrir wa Tanwir". Results. In it, we find an unprecedented mechanism among rhetorical tools, known as the "Syntactic Dependency" mechanism. Through this mechanism, Ibn Ashur is able to derive new hidden meanings, elevating the status of his tafsir to a pioneering position among Islamic tafsir works. This study presents examples of the hidden meanings he unearthed by using the "Syntactic Dependency" mechanism. Conclusion. Hence, their books have diversified and multiplied as these mechanisms have evolved.